Genome-wide analysis of FRF gene family and functional identification of HvFRF9 under drought stress in barley - He, Xiaoyan; He, Yaru; Dong, Yihuan; Gao, Yu; Sun, Xingcai; Chen, Weiyue; Xu, Xintong; Su, Congjun; Lv, Yifan; Ren, Boyu; Yin, Huayan; Zeng, Jianbin; et al. (Frontiers in Plant Science, 2024)
FHY3 and its homologous protein FAR1 are the founding members of FRS family. They exhibited diverse and powerful physiological functions during evolution, and participated in the response to multiple abiotic stresses. FRF genes are considered to be truncated FRS family proteins. They competed with FRS for DNA binding sites to regulate gene expression. However, only few studies are available on FRF genes in plants participating in the regulation of abiotic stress. With wide adaptability and high stress-resistance, barley is an excellent candidate for the identification of stress-resistance-related genes. In this study, 22 HvFRFs were detected in barley using bioinformatic analysis from whole genome. According to evolution and conserved motif analysis, the 22 HvFRFs could be divided into subfamilies I and II. Most promoters of subfamily I members contained abscisic acid and methyl jasmonate response elements; however, a large number promoters of subfamily II contained gibberellin and salicylic acid response elements. HvFRF9, one of the members of subfamily II, exhibited a expression advantage in different tissues, and it was most significantly upregulated under drought stress. In-situ PCR revealed that HvFRF9 is mainly expressed in the root epidermal cells, as well as xylem and phloem of roots and leaves, indicating that HvFRF9 may be related to absorption and transportation of water and nutrients. The results of subcellular localization indicated that HvFRF9 was mainly expressed in the nuclei of tobacco epidermal cells and protoplast of arabidopsis. Further, transgenic arabidopsis plants with HvFRF9 overexpression were generated to verify the role of HvFRF9 in drought resistance. Under drought stress, leaf chlorosis and wilting, MDA and O2− contents were significantly lower, meanwhile, fresh weight, root length, PRO content, and SOD, CAT and POD activities were significantly higher in HvFRF9-overexpressing arabidopsis plants than in wild-type plants. Therefore, overexpression of HvFRF9 could significantly enhance the drought resistance in arabidopsis. These results suggested that HvFRF9 may play a key role in drought resistance in barley by increasing the absorption and transportation of water and the activity of antioxidant enzymes. This study provided a theoretical basis for drought resistance in barley and provided new genes for drought resistance breeding.